2016
DOI: 10.1111/idj.12211
|View full text |Cite
|
Sign up to set email alerts
|

Oral and maxillofacial pathology submitted to Rizgary Teaching Hospital: a 6-year retrospective study

Abstract: Many of our findings are consistent with those reported in the literature. However, a relatively larger proportion of neoplastic lesions were found in our cohort and in other Iraqi centres. Of concern to practising clinicians in Iraq is that one in 10 biopsies submitted was a squamous cell carcinoma and three in 20 accessions were malignant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…This is in accordance with other studies, which reported a high prevalence of oral lesions in males . However, this is in contrast to studies from Iraq and Saudi Arabia where oral lesions were found to be more prevalent among females . Specific lesions appeared to have a strong predilection for either sex.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This is in accordance with other studies, which reported a high prevalence of oral lesions in males . However, this is in contrast to studies from Iraq and Saudi Arabia where oral lesions were found to be more prevalent among females . Specific lesions appeared to have a strong predilection for either sex.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study in Iraq reported pyogenic granulomas to be the most common lesion and comprised 10.5% of all lesions compared to 6.17% in our study. However, it mostly occurred in the tongue in Yakin et al's study …”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations